Evaluating the performance of kindergarten teachers according to quality assurance standards in the Kurdistan Region / Iraq - Shaelan Ahmed Hamadameen; Salwa Ahmed Ameen (Zanco Journal of Humanity Sciences)
This research aimed to the following objectives: Constructing a performance standards for kindergarten teachers in the light of quality assurance, identifying the performance level of kindergarten teachers in light of quality assurance standards, where the researchers used the descriptive approach to suit the nature of the research, and the research community was identified from kindergarten teachers in Kurdistan Region for the year In order to achieve the objectives of the current research, the researchers built performance criteria for parameters, and for this purpose, the construction sample (statistical analysis) was selected from the original community by 15%, as the construction sample amounted to (409) parameters. Where it was chosen by a stratified random method, and after applying the measures of building the scale, the researchers built a measure of performance standards parameters consisting of (87) paragraphs in the form of declarative phrases, distributed on (10) areas (16) standards, and these areas included each of: Effective education strategy: (9, paragraph), planning and follow-up (8, paragraph), classroom activities management and positive interaction: (8, paragraph), learning methods that respond to children’s needs for their development (8, paragraph), environmental awareness (8, paragraphs), child health and safety (8, paragraphs), professional development and knowledge of specialization: (10, paragraph), enhancing communication with the child: (8, paragraphs), the teacher’s partnership with the family and society (10, paragraphs), evaluation: (10, paragraphs) and it consists of ( 5) Five answer alternatives, which extracted the appropriate psychometric characteristics of the scale items, which included: (discriminatory power, item reliability and item stability), and extracted the psychometric properties of the scale, which included: (apparent honesty and constructive honesty), and stability: (retest method and Cronbach's alpha equation), and to apply the scale in its final form, the researcher chose the sample application from the original population with a percentage (10%), with a number of (732) parameters, which were chosen by a stratified random method, and based on the (SPSS) program (Statistical Portfolio for Social Sciences) to analyze data, the current research reached the most important results according to the objectives of the research as follows: Building criteria Performance of kindergarten teachers in the light of quality assurance in the Kurdistan Region of Iraq - consisting of (87) paragraphs in the form of declarative phrases with appropriate psychometric characteristics, and that the kindergarten teachers in the center of the governorates of the Kurdistan Region of Iraq are characterized by the performance of female teachers in general and at a high level, and in conclusion and in In light of the research results, the researchers reached some recommendations and suggestions.